2021
DOI: 10.1088/1755-1315/887/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution on Recovery Strategy Due to The Impact of The Covid-19 Pandemic on The Conditions of Micro Small Medium Enterprises (MSME’s) in Central Java Province, Indonesia

Abstract: MSMEs are the backbone of the economy in Indonesia. However, most MSMEs were collapse due to the Covid-19 pandemic. Therefore, MSMEs recovery is needed to restore the real sector, particularly in Central Java. The study analyses the impact and economic recovery strategies during and after Covid-9 in the MSME sector. The research used a descriptive qualitative method. Data were collected by electronic survey and in-depth interviews and analyzed by SWOT. The results showed the Covid-9 pandemic significantly redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Various policies, such as loan schemes, subsidies, and tax incentives, have been implemented to support sustainable growth and encourage new entrepreneurship (Hadi et al, 2023). Financing for MSMEs, a vital element in government policies, is still dominated by informal financing sources (Widiastuti et al, 2021). Bank loans, non-bank financial institutions, and venture capital remain primary sources, but MSMEs have increasingly looked for formal financial sources to reduce the dependence on informal financing (Esubalew & Raghurama, 2023;Susan, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Various policies, such as loan schemes, subsidies, and tax incentives, have been implemented to support sustainable growth and encourage new entrepreneurship (Hadi et al, 2023). Financing for MSMEs, a vital element in government policies, is still dominated by informal financing sources (Widiastuti et al, 2021). Bank loans, non-bank financial institutions, and venture capital remain primary sources, but MSMEs have increasingly looked for formal financial sources to reduce the dependence on informal financing (Esubalew & Raghurama, 2023;Susan, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The survey conducted by Widiastuti et al (2021) on the impact of the COVID-19 pandemic on the performance of Micro, Small, and Medium Enterprises (MSMEs) provides evidence of the government's ineffective policies and strategies in promoting their development. The study encompassed a total of 679 participants whose primary vocation was identified as company operators.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has prompted governments to take radical steps to contain the virus and protect their citizens (Lee et al, 2020;Goodyear-Smith et al, 2020;Devi, 2020). These included successive restrictions on social distance, which have led to closing many enterprises in various industries and dismissing their employees (Kassa, 2021;Lesi, 2020;Widiastuti et al, 2021). The introduction of restrictions has significantly weakened the economies of many countries, and stock markets have started to record sharp declines (Cox et al, 2020).…”
Section: Introductionmentioning
confidence: 99%